Prevalence of familial hypercholesterolemia in patients with acute coronary syndrome - Željka Dragila; Matea Lozert; Silvija Canecki-Varžić; Kristina Selthofer-Relatić (Medicinski glasnik, 2023)
Aim: To investigate the prevalence of familial hypercholesterolemia in patients with acute coronary syndrome (ACS). Methods: The study included fifteen patients with first or repeated ACS and treated/nontreated dyslipidaemia admitted to the Department of Cardiovascular Diseases of Clinical Hospital Centre Osijek between 1 January 2020 and 1 January 2021. The cut-off value of low-density lipoprotein (LDL)-C was 4.5mmol/L as a possible cut-off value for familial hypercholesterolemia presence. Data were collected from medical history and during patient’s follow-up. Results: Included patients that fulfilled criteria were predominantly male - 14 (93%), mean age 61 years. The median level of LDL cholesterol at admission because of ACS was 5.14 mmol/L, whereas the follow-up level after one year was 2.27 mmol/L (p=0.001). At first follow-up, 7 (46%) patients were treated with atorvastatin 80 mg or rosuvastatin 40 mg, 3 (20%) atorvastatin 80mg + ezetimibe 10mg, 2 (13%) with rosuvastatin 40 mg+ ezetimibe 10 mg, other patients were treated with a lower dose of statin or ezetimibe. According to LDL-C profile and by calculating the Dutch Lipid Clinic Network Score, one (of 15) patient was categorized as having definite familial hypercholesterolemia and two (of 15) as having probable familial hypercholesterolemia leading to the use of triple hypolipidemic therapy (statin+ezetimibe+PCSK9 inhibitor) in 2 (13%) patients (one female and one male). Conclusion: LDL-C level of 4.5 mmol/L and higher represents an indication for screening for familial hypercholesterolemia in patients with ACS. The prevalence of familial hypercholesterolemia in ACS, estimated by the Dutch Lipid Clinic Network Score, could be higher than previously reported.
Keywords: atherosclerosis; LDL cholesterol; PCSK9 Inhibitors